Communicating User Experience: Applying Local Strategies Research to Digital Media Design - Milburn, Trudy (2015)
Communicating User Experience illustrates how the use of Local Strategies Research (LSR) methodologies enables designers to understand the cultural implications for user actions and practices in a...
Keywords: dept.aa

Preface: Special Issue—College Experiences for Students with Autism Spectrum Disorder - Jackson, Scott L. J.; Hart, Logan; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Keywords: dept.aa; dept.sed

Effects of Upper-Limit Water Temperatures on the Dispersal of the Asian Clam Corbicula fluminea - Rosa, Inês Correia; Pereira, Joana Luísa; Costa, Raquel; Gonçalves, Fernando; Prezant, Robert (PLOS ONE, 2012)
Temperature is a determinant environmental variable in metabolic rates of organisms ultimately influencing important physiological and behavioural features. Stressful conditions such as increasing temperature, particularly within high ranges occurring in the summer, have been suggested to induce flotation behaviour in Corbicula fluminea which may be important in dispersal of this invasive species. However, there has been no experimental evidence supporting this hypothesis. It was already proven that C. fluminea drift is supported by a mucilaginous drogue line produced by mucocytes present in the ctenidia. Detailed microscopic examination of changes in these cells and quantification of clam flotation following one, two and three weeks of exposure to 22, 25 and 30°C was carried out so that the effects of increasing water temperatures in dispersal patterns could be discussed. Results show that changes in temperature triggered an acceleration of the mucocytes production and stimulated flotation behaviour, especially following one week of exposure. Dilution of these effects occurred following longer exposure periods. It is possible that these bivalves perceive changing temperature as a stress and respond accordingly in the short-term, and then acclimate to the new environmental conditions. The response patterns suggest that increasing water temperatures could stimulate C. fluminea population expansion.
23 citations (Crossref) [2023-10-31]
Keywords: Analysis of variance; Animal behavior; Behavior; Bivalves; Crystallization; Histology; Invasive species; Sediment; dept.aa; peer-reviewed

Growing routes: Rhetoric as the study and practice of movement - Crawford, I.W. (Rhetorica in Motion: Fem. Rhetorical Methods and Methodologies, 2010)
Journal Abbreviation: Rhetorica in Motion: Fem. Rhetorical Methods and Methodologies
Keywords: dept.aa

Challenges of transitioning from a faculty to an administrative role: part 3, from solving problems to managing polarities. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
3 citations (Crossref) [2023-10-31] Place: United States Thompson, Cesarina M. School of Health & Human Services, Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Education; Nursing; *Efficiency; Organizational; *Faculty; Nursing; *Leadership; *Nurse Administrators; *Professional Role/px [Psychology]; Curriculum; Education; Nursing; Efficiency; Organizational; Faculty; Nursing; Humans; Leadership; Nurse Administrators; Professional Role; Time Factors; article; curriculum; dept.aa; human; leadership; nurse administrator; nursing education; organization and management; peer-reviewed; professional standard; psychological aspect; time

Challenges of transitioning from a faculty to an administrative role: part 2, moving from individual contributor to group leader. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
1 citations (Crossref) [2023-10-31] Place: United States Thompson, Cesarina M. School of Health & Human Services, Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Faculty; Nursing; *Group Processes; *Leadership; *Nurse Administrators; Education; Nursing; Faculty; Nursing; Group Processes; Humans; Leadership; Nurse Administrators; Schools; Nursing; Social Support; article; dept.aa; group process; human; leadership; nurse administrator; nursing education; peer-reviewed; social support

Transitioning from a faculty to an administrative role: part 1, moving from individual to collective accountability. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
2 citations (Crossref) [2023-10-31] Place: United States Thompson, Cesarina M. School of Graduate Studies, Southern Connecticut State University, New Haven, USA.
Keywords: *Career Mobility; *Faculty; Nursing/og [Organization & Administration]; *Nurse Administrators/og [Organization & Administration]; *Professional Role; Career Mobility; Employee Performance Appraisal; Faculty; Nursing; Humans; Leadership; Nurse Administrators; Professional Role; United States; article; career mobility; dept.aa; human; leadership; nurse administrator; nursing education; organization and management; peer-reviewed; personnel management; professional standard

Handheld app offering visual support to students with autism spectrum disorders (ASDs) - Zamfir, Bogdan; Tedesco, Robert; Reichow, Brian (International Conference on Computers Helping People with Special Needs, 2012)
iPrompts® is a software application for handheld devices that provides visual support to individuals with Autism Spectrum Disorders (ASDs). Caregivers use the application to create and present visual schedules, visual countdown timers, and visual choices, to help individuals with ASDs stay organized, understand upcoming events, and identify preferences. The developer of the application, HandHold Adaptive, LLC, initially introduced iPrompts on the iPhone and iPod Touch in May of 2009. The research team from the Center of Excellence on Autism Spectrum Disorders at Southern Connecticut State University conducted a study of iPrompts in 2010, investigating its use by educators working with students with ASDs. Among other findings, educators indicated a desire to present visual supports on a larger, "tablet"-sized display screen, leading the developer to produce an iPad-specific product, iPrompts® XL. Described in this paper are the research effort of iPrompts and subsequent development effort of iPrompts XL. © 2012 Springer-Verlag.
7 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: ASD; Applications; Autism spectrum disorders; Diseases; Education; Hand held computers; Hand held device; Smartphones; app; application; autism spectrum disorder; dept.aa; handheld device; iPad; iPhone; iPrompts; smartphone; tablet

The potential of repetitive transcranial magnetic stimulation for autism spectrum disorder: A consensus statement - Cole, Eleanor J.; Enticott, Peter G.; Oberman, Lindsay M.; Gwynette, M. Frampton; Casanova, Manuel F.; Jackson, Scott L. J.; Jannati, Ali; McPartland, James C.; Naples, Adam J.; Puts, Nicolaas A. J.; Albein-Urios, Natalia; Barnett, Carol; et al. (Biological Psychiatry, 2019)
Autism spectrum disorder (ASD) affects approximately 1 in 59 children, but there are currently no biomedical treatments available that target the core symptoms (1). Preliminary evidence suggests that repetitive transcranial magnetic stimulation (rTMS) may have the potential to alleviate difficulties experienced by individuals with ASD (2). The evidence supporting the use of rTMS for ASD has led researchers in the field to form a consensus group that has met annually since 2014. Here we summarize discussions from the most recent meeting in May 2017, including recommendations for future research directions.
24 citations (Crossref) [2023-10-31]
Keywords: dept.aa; peer-reviewed

Mood Disorders in High-Functioning Autism: The Importance of Alexithymia and Emotional Regulation. - Morie, Kristen P; Jackson, Scott; Zhai, Zu Wei; Potenza, Marc N; Dritschel, Barbara (Journal of Autism and Developmental Disorders, 2019)
Individuals with autism spectrum disorder (ASD) often have co-morbid anxiety and depression. Alexithymia and emotion regulation difficulties are commonly seen in individuals with ASD and in mood disorders. We hypothesized that alexithymia and emotional regulation would mediate the relationship between autistic features and anxiety/depression symptom severity. We collected data about emotional regulation, alexithymia, autistic symptoms and depression/anxiety in a sample of 64 young adults with ASD. We constructed two serial multiple mediator models, using autistic features as the independent variable and anxiety/depression symptoms as outcome variables. The serial relationship between alexithymia and emotional regulation mediated associations between autistic features and depression and anxiety, separately. The findings suggest that targeting alexithymia may benefit therapies designed to alleviate mood disorders in ASD.
43 citations (Crossref) [2023-10-31] Place: United States Morie, Kristen P. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. kristen.morie@yale.edu. Morie, Kristen P. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. kristen.morie@yale.edu. Jackson, Scott. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. Scott.Jackson@yale.edu. Jackson, Scott. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. Scott.Jackson@yale.edu. Jackson, Scott. Office of Assessment and Analytics, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515, USA. Scott.Jackson@yale.edu. Zhai, Zu Wei. Department of Psychology, Middlebury College, Middlebury, VT, 05753, USA. Potenza, Marc N. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Department of Neuroscience, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Connecticut Council on Problem Gambling, Wethersfield, CT, 06109, USA. Potenza, Marc N. Connecticut Mental Health Center, New Haven, CT, 06519, USA. Dritschel, Barbara. School of Psychology & Neuroscience, University of St Andrews, St. Andrews, Fife, KY16 9JP, UK.
Keywords: *Affective Symptoms/px [Psychology]; *Autism Spectrum Disorder/px [Psychology]; *Emotions; *Mood Disorders/px [Psychology]; ASD; Adolescent; Adult; Affective Symptoms; Affective Symptoms/ep [Epidemiology]; Aged; Alexithymia; Anxiety; Anxiety Disorders; Article; Asperger Syndrome; Asperger syndrome; Autism; Autism Spectrum Disorder; Comorbidity; Depression; Emotional regulation; Emotions; Female; Humans; Male; Middle Aged; Mood Disorders; Mood disorders; Self Report; Surveys and Questionnaires; Toronto Alexithymia scale; Young Adult; adolescent; adult; aged; alexithymia; anxiety; anxiety disorder; autism; comorbidity; controlled study; depression; dept.aa; dept.adm; emotion; emotional disorder; emotionality; female; human; major clinical study; male; mental health; middle aged; mood disorder; peer-reviewed; priority journal; psychology; questionnaire; self report; young adult

Microplastic abundances in a mussel bed and ingestion by the ribbed marsh mussel Geukensia demissa. - Khan, Matthew B; Prezant, Robert S (Marine Pollution Bulletin, 2018)
Human activities have generated large quantities of microplastics that can be consumed by filter-feeding organisms as potential food sources. As a result, organisms may experience marked reductions in growth and/or health. To date there has been no investigations connecting microplastics (MPs) with the critically important ribbed mussel Geukensia demissa. Here we examined MP abundances within a bed of G. demissa in New Jersey. Results indicate that MP densities ranged between 11,000-50,000pieces/m2. The abundance of larger MPs (5mm>=1mm) did not vary among sampling sites while the smaller MPs (<1mm) abundances did vary between sampling sites. These smaller MPs also accounted for 79% of MPs recovered from these sites. Based on the higher abundance of smaller MPs, we also investigated MP ingestion/rejection in a laboratory setting. These results confirmed that ribbed mussels can ingest MPs with negative consequences for the buoyancy of plastics rejected in feces and pseudofeces. Copyright © 2018 The Authors. Published by Elsevier Ltd.. All rights reserved.
39 citations (Crossref) [2023-10-31] Place: England Khan, Matthew B. Montclair State University, 1 Normal Avenue, Montclair, NJ 07043, USA; The Georgia Sea Turtle Center, Jekyll Island Authority, 214 Stable Road, Jekyll Island, GA 31527, USA. Electronic address: khanm11@montclair.edu. Prezant, Robert S. Department of Environment, Geography and Marine Sciences, Southern Connecticut State University, New Haven, CT 06515, USA. Electronic address: prezantr1@southernct.edu.
Keywords: *Bivalvia; *Plastics/an [Analysis]; *Waste Products/an [Analysis]; *Water Pollutants; Chemical/an [Analysis]; Animals; Article; Bivalvia; Contamination; Eating; Filter-feeding organisms; Geukensia demissa; Human activities; Humans; Ingestion; Ingestion (engines); Marine pollution; Microplastic; Microplastics; Molluscs; Mussel bed; New Jersey; Plastics; Sampling site; United States; Waste Products; Water Pollutants; Chemical; abundance; analysis; animal; animal experiment; animal tissue; bivalve; body fluids and secretions; controlled study; dept.aa; eating; feces; filter feeder; growth; human; human activities; ingestion; ingestion rate; marine pollution; marsh; microplastic; mussel; nonhuman; peer-reviewed; plastic; pseudofeces; sampling; unclassified drug; waste; water pollutant

Brief report: Self-reported academic, social, and mental health experiences of post-secondary students with autism spectrum disorder - Jackson, Scott L. J.; Hart, Logan; Brown, Jane Thierfeld; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
104 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Visioning hope: embracing higher education's role with urban public charter schools - Bergeron, Bette S. (Urban Education, 2017)
The purpose of this study is to reflect on the evolution of a partnership between a university and urban charter high school serving a predominately African American population. Because of the author's embeddedness both as the researcher and participant member, this research assumes the paradigm of autoethnography. Reflections on key components of this evolution provide implications for teacher education, particularly in regard to a call for engagement between urban charter schools and educator preparation programs, and a challenge to higher education to analyze existing perceptions of public charter schools within a wider institutional mission to prepare educators for all children.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-392-571-564-728 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: African American students; charter school; dept.aa; high school; programs; teacher education; universities; urban education

Transition issues and challenges for youth with autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L. J.; Hart, Logan (Pediatric Annals, 2017)
49 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Autism: Social communication disorder - Jackson, Scott Luther James (Encyclopedia of Autism Spectrum Disorders, 2017)
Keywords: dept.aa